Quantitative Analysis of the Efficacy of PARP Inhibitors as Maintenance Therapy in Recurrent Ovarian Cancer - Gao, Lili; Chen, Rui; Li, Ting; Li, Lujin; Zheng, Qingshan (Frontiers in Pharmacology, 2021)
Objective: This study aim to establish a pharmacodynamic model and screen reasonable covariates in order to quantitatively describes poly (ADP-ribose) polymerase inhibitors (PARPis)’ efficacy for maintenance treatment of recurrent ovarian cancer (ROC). Methods: The log normal hazard function model was established by using progression free survival (PFS) data from 1169 patients from published randomized trials with regards to the FDA approved PARP inhibitors (olaparib, niraparib, and rucaparib). Using Monte Carlo simulation to compare PFS values in different scenarios, such as monotherapy therapy (administered alone) and combination therapy (PARPis combination with chemo- or target-therapies), different biomarkers status, different PARP inhibitors et.al. Progression free survival (PFS) was estimated. Results: The study showed the median PFS was 8.5 months (mons) in monotherapy, and 16 mons in combination therapy. The median PFS of BRCA mutation, BRCA wild-type and HRD-positive patients was 11, 7.5 and 9 mons in monotherapy, respectively, and 23, 14 and 17.5 months in combination therapy, respectively. Also the results showed the median PFS of olaparib, niraparib, and rucaparib monotherapy were about 9.5, 10.5 and 12 mons, respectively, and about 19, 20 and 25 mons in combination therapy, respectively. The median PFS values in combination with cediranib, bevacizumab, and chemotherapy were about 17, 12.5 and 19.5 mons, respectively. Conclusions: PARPi combination therapy will achieve higher effectiveness in maintenance treatment of ROC than monotherapy, and the efficacy of PARPis in combination with chemotherapy is higher than that of in combination with antiangiogenic drugs. The PFS of BRCA wild-type was similar to that of HRD-positive patients, and there was no significant difference in PFS among approved olaparib, niraparib, and rucaparib.The above information provides necessary quantitative information for the clinical practice of PARPis in the treatment of ROC.